Polygamy and Socioeconomic Factors in Islamic Family Law: Legal Interpretations and Social Outcomes - Mahmud, Jihanu Rofifah (Journal of Islamic Family Law, 2025)
This research aims to explore how socioeconomic factors influence the interpretation and practice of polygamy within Islamic family law and examine the resulting social impacts on families and communities. Purposive sampling technique is used to select jurisdictions with varying socioeconomic contexts. Semi-structured interviews with religious scholars, legal experts, and affected individuals will provide qualitative insights into the lived experiences of those involved in polygamous marriages. Data analysis will be conducted using thematic analysis to identify recurring themes and patterns, focusing on how socio-economic factors shape legal interpretations and social outcomes for families. The findings indicate that while Islamic law provides a framework for regulating polygamies, the socio- economic context significantly influences its interpretation and enforcement. The study suggests that Islamic jurisdictions implement more stringent financial requirements, similar to the practices in Morocco and Malaysia. This study underscores the need for legal frameworks that are sensitive to socioeconomic realities, emphasizing the importance of financial stability as a criterion for polygamic marriages to align with Islamic principles of fairness.